Intergrasi IoT dan Machine Learning untuk Sekolah Pintar (Smart School) - Fathiah Fathiah; Rizki Julia Utama; Muhammad Rizal Fachri; Miftahul Jannah (Bansigom Na Publisher, 2025)
The integration of the Internet of Things (IoT) and Machine Learning (ML) offers significant potential in developing the Smart School concept. IoT technology enables real-time data collection from various devices within the school environment, while ML analyzes this data to provide valuable insights. This study explores the role of IoT in monitoring aspects such as student attendance, energy consumption, and school security, alongside the application of ML to enhance operational efficiency and learning quality. The outcomes of this integration include resource optimization, early problem detection, and personalized teaching-learning processes. The paper also evaluates challenges such as data security and technological infrastructure and provides recommendations for effective implementation. With a holistic approach, this research aims to guide schools in adopting smart technologies to support more effective, secure, and sustainable education.